Multiplex identification of sepsis‐causing Gram‐negative pathogens from the plasma of infected blood. Issue 4 (14th December 2017) - Chung, Boram; Park, Chulmin; Cho, Sung‐Yeon; Shin, Juyoun; Shin, Sun; Yim, Seon‐Hee; Lee, Dong‐Gun; Chung, Yeun‐Jung
Abstract: Early and accurate detection of bacterial pathogens in the blood is the most crucial step for sepsis management. Gram‐negative bacteria are the most common organisms causing severe sepsis and responsible for high morbidity and mortality. We aimed to develop a method for rapid multiplex identification of clinically important Gram‐negative pathogens and also validated whether our system can identify Gram‐negative pathogens with the cell‐free plasm DNA from infected blood. We designed five MLPA probe sets targeting the genes specific to major Gram‐negative pathogens ( uidA and lacY for E. coli, ompA for A. baumannii, phoE for K. pneumoniae, and ecfX for P. aeruginosa ) and one set targeting the CTX‐M group 1 to identify the ESBL producing Gram‐negative pathogens. All six target‐specific peaks were clearly separated without any non‐specific peaks in a multiplex reaction condition. The minimum detection limit was 100 fg of pathogen DNA. When we tested 28 Gram‐negative clinical isolates, all of them were successfully identified without any non‐specific peaks. To evaluate the clinical applicability, we tested seven blood samples from febrile patients. Three blood culture positive cases showed E. coli specific peaks, while no peak was detected in the other four culture negative samples. This technology can be useful for detection of major sepsis‐causing, drug‐resistant Gram‐negative pathogens and also the major ESBL producing Gram‐negatives from the blood of sepsis patients in a clinical setting. This system can help early initiation of effective antimicrobial treatment against Gram‐negative pathogens for sepsis patients, which is very crucial for better treatment outcomes.